Rol de la enfermera en hábitos nutricionales del paciente diabético en edades 39 a 85 años que acuden al Dispensario San Luis 3 del Seguro Social Campesino del cantón Mocache, provincia de Los Ríos, en el primer semestre del año 2013 - Chasi Tonato, Aída Mariana (2013)
Diabetes Mellitus is a disease that afflicts about 170 million people in the world (according to OMS). Although not yet found a cure for it, if you know that a good treatment, involving a proper and well balanced diet can help prevent the consequences that brings The purpose of this research is to determine the role of the nurse in nutritional habits of diabetic patients aged 39-85 years attending the Dispensary San Luis 3 Rural Social Security Mocache from Canton, Province De Los Rios in the first half of the year 2013 The methods used in this research are scientific, descriptive, inductive and deductive, which makes the research more comprehensive and analytical. Based on these final results of the investigation will be established